Accelerating employability for adult learners through online expansion. Issue 5 (February 2017) - Sutton, Halley
Abstract : ANAHEIM, Calif. — The recent recession saw 8.7 million American jobs lost. Among those who lost jobs, 80 percent had no formal postsecondary education. And projections show that to stay competitive in the next 10 years, 72 percent of those who are currently employed will need additional education to keep up with the advances in technology in their fields. In marketing to adult learners, institutions must factor into consideration what the needs of those adult learners might be — most often, a desire to improve their financial circumstances and attain marketable job skills, whether through certification or a degree.